Economic costs of veterinary drug and antibiotic use in commercial dairy cattle herds in Central European countries - Ozsvári, László; Máté, Marietta (Frontiers in Veterinary Science, 2026)
Antimicrobial use in livestock production is a critical issue in terms of both animal health and public health, particularly due to its role in the emergence of antimicrobial resistance (AMR). In this study, the veterinary drug costs, with a particular focus on antibiotics, were surveyed in 20 commercial dairy cattle herds comprising a total of 18,653 cows in five Central-European countries (Czechia, Hungary, Serbia, Slovakia, and Slovenia) in 2019. The distribution of veterinary drug costs by product groups and indication, as well as the antibiotic usage by indication and class of active substance, were assessed. In 2019, the average veterinary drug cost per cow was €63.3, ranging from €29.0 in Czechia to €99.0 in Slovenia. Regarding the product groups the antibiotics were responsible for the largest cost share (40.8%; €25.8), followed by hormones (19.1%), surgical and medical products (13.7%), vaccines (13.1%), vitamins and supplements (8.7%), and antiparasitics (4.5%). By indication the highest proportions of total veterinary drug cost were related to mastitis (32.2%), reproductive disorders (22.9%), lameness (11.3%), and respiratory diseases (10.0%). Furthermore, 60.0% of the total antibiotic costs were used for mastitis treatments, followed by lameness (23.5%), respiratory and digestive diseases (11.5%), and reproductive failures (5.0%). Regarding antibiotic classes, cephalosporins alone represented 43.7% of the total antibiotic costs, followed by various combinations (e.g., penicillins and aminoglycosides, amoxicillin with clavulanic acid) at 21.2%, and penicillins alone at 9.6%. Fluoroquinolones, tetracyclines, macrolides were used to a lesser extent. In udder treatments, cefquinome, cefoperazone and cefapirin were the most widely applied antibiotics. Ceftiofur and cefquinome were frequently used for lameness cases, while tilmicosin, tulathromycin, and tildipirosin were common for respiratory and digestive disorders. Reproductive failures were predominantly treated with cefapirin and chlortetracycline. Our results show that Central European dairy cattle farms allocated the largest share of their veterinary drug expenditures to antibiotics, mainly due to the extensive use of intramammary infusions containing cephalosporins, penicillins, and aminoglycosides in mastitis treatments. However, considerable differences in veterinary drug and antibiotic use were observed between herds.